Slow intestinal transit contributes to elevate urinary p‐cresol level in Italian autistic children. Issue 7 (6th October 2015) - Gabriele, Stefano; Sacco, Roberto; Altieri, Laura; Neri, Cristina; Urbani, Andrea; Bravaccio, Carmela; Riccio, Maria Pia; Iovene, Maria Rosaria; Bombace, Francesca; De Magistris, Laura; Persico, Antonio M.
Abstract : The uremic toxin p ‐cresol (4‐methylphenol) is either of environmental origin or can be synthetized from tyrosine by cresol‐producing bacteria present in the gut lumen. Elevated p ‐cresol amounts have been previously found in the urines of Italian and French autism spectrum disorder (ASD) children up until 8 years of age, and may be associated with autism severity or with the intensity of abnormal behaviors. This study aims to investigate the mechanism producing elevated urinary p ‐cresol in ASD. Urinary p ‐cresol levels were thus measured by High Performance Liquid Chromatography in a sample of 53 Italian ASD children assessed for (a) presence of Clostridium spp. strains in the gut by means of an in vitro fecal stool test and of Clostridium difficile ‐derived toxin A/B in the feces, (b) intestinal permeability using the lactulose/mannitol (LA/MA) test, (c) frequent use of antibiotics due to recurrent infections during the first 2 years of postnatal life, and (d) stool habits with the Bristol Stool Form Scale. Chronic constipation was the only variable significantly associated with total urinary p ‐cresol concentration ( P < 0.05). No association was found with presence of Clostridium spp. in the gut flora ( P = 0.92), augmented intestinal permeability ( P = 0.18), or frequent use of antibiotics in early infancy ( P = 0.47). No ASD child was found to carry C. difficile in the gut or to release toxin A/B in the feces. In conclusion, urinary p ‐cresol levels are elevated in young ASD children with increased intestinal transit time and chronic constipation. Autism Res 2016, 9: 752–759 . © 2015 International Society for Autism Research, Wiley Periodicals, Inc.